2008
DOI: 10.1007/s10494-008-9156-0
|View full text |Cite
|
Sign up to set email alerts
|

Some Swirling-flow Challenges for Turbulent CFD

Abstract: An International Journal published in association with ERCOFTAC• Topics cover fluid dynamics, scalar transport, multi-physics interactions and flow/turbulence control, analytical, computational and experimental methods• Emphasis on novelty, originality, timeliness, quality and thematic relevance to engineering and environmental applications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…It is now well known RANS based eddy viscosity models, such as the k-ǫ model perform very poorly in strongly swirling flows. Second moment closures fare somewhat better, see for example Craft et al (2008), although even these appear to be incapable of accurately reproducing the unsteady large scale structures that appear in strongly swirling confined flows. Both LES and unsteady RANS were applied in Dunham et al (2009) to model the flow in a single swirl stream fuel injector where the capability of LES to reproduce flow characteristics was shown to be in excellent agreement with measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well known RANS based eddy viscosity models, such as the k-ǫ model perform very poorly in strongly swirling flows. Second moment closures fare somewhat better, see for example Craft et al (2008), although even these appear to be incapable of accurately reproducing the unsteady large scale structures that appear in strongly swirling confined flows. Both LES and unsteady RANS were applied in Dunham et al (2009) to model the flow in a single swirl stream fuel injector where the capability of LES to reproduce flow characteristics was shown to be in excellent agreement with measurements.…”
Section: Introductionmentioning
confidence: 99%
“…There is no effect of inflow condition (turbulence level) and the flow can also involve multiple regimes such as laminar, transitional, fully turbulent and relaminarization. A renewed interest for these flows was born from the appearance of precessing large scale vortical structures embedded in the turbulent regime, first observed experimentally by [5] and confirmed numerically by the URANS computations of [4].…”
Section: Introductionmentioning
confidence: 99%
“…Craft et al [15] performed URANS simulations of the above mentioned experiments. The simulation of the disk cavity was done using a two-equation turbulence model, and similar to the results presented in this report, Craft's simulations did not reach stability even after 70 revolutions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the sealing effectiveness (g c ) is not predicted accurately. Craft et al [15] showed in his simulation of disk cavities using a two-equation turbulence model that the flow does not reach steady state even after 70 revolutions. The present work simulates the experimental rig geometry of Balasubramanian et al [16] in a 360 unsteady CFD model, runs the simulation under rig conditions, and then compares the CFD predictions of pressure, velocity, and concentration-based cavity effectiveness (g c ) with the experimental data of [16].…”
Section: Introductionmentioning
confidence: 99%